Equity Crowdfunding Vs Cybercrime: A Legal Protection - Yeon, Asmah Laili (Bangladesh Institute of Legal Development, 2022)
Equity Crowdfunding (ECF) is a type of financial support that enables a start-up to acquire principal to run a companies by way of small equity investments by using online portals to advertise and promote such proposals to public shareholders. Since the modus operandi of ECF is using Internet platform, such fundraising therefore, it is not immune to fraud. The article aim is to evaluate the legal protection of cybercrime to the issuers, platform distributers and ECF business investors in Malaysia. For this study, doctrinal legal investigation has been employed by scrutinizing the legislations governing ECF in Malaysia particularly Capital Market and Services Act 2007 (Act 671) (CMSA 2007) and Securities Commission’s Guidelines on Recognized Markets 2020 (GRM 2020). Whether the existing legislations are appropriate in respect to ECF to combat cybercrime? The study found that there are numerous legal problems concerning ECF Company in Malaysia; Issuers and Recognized Market Operator contracts, privacy and personal data protection, cybercrime, compliance with public offering rules and guidelines, and registration procedures and their challenges. Even while the CMSA 2007 and GRM 2020 govern ECF commerce, other related regulations like CCA 1997, CMA 1998, and others also apply to cybercrimes committed in the ECF market. Some provisions pertaining to ECF cybercrime have gaps in them. The current legal framework should place more emphasis on addressing fraud and the possibility of intellectual theft by other parties